2020
DOI: 10.1101/2020.07.06.190066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Transgenic and Adenovirus hACE2 Mouse Models for SARS-CoV-2 Infection

Abstract: AbstractSevere acute respiratory syndrome CoV-2 (SARS-CoV-2) is currently causing a worldwide pandemic with high morbidity and mortality. Development of animal models that recapitulate important aspects of coronavirus disease 2019 (COVID-19) is critical for the evaluation of vaccines and antivirals, and understanding disease pathogenesis. SARS-CoV-2 has been shown to use the same entry receptor as SARS-CoV-1, human angiotensin-converting enzyme 2 (hACE2)(1-3). Due to amino acid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
136
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(152 citation statements)
references
References 64 publications
(100 reference statements)
14
136
2
Order By: Relevance
“…While these studies suggest that the hACE2 mRNA transfection into the Ifnar1 -/mice did not increase the susceptibility of the Ifnar1 -/mice to SARS-CoV-2 it is possible that the dose and route of infection as well as the harvest time points we chose for these studies were not optimal for detection of infectious virus. Previous studies have shown that administration of higher doses of virus by the intranasal route did lead to the detection of virus in mice which had been induced to express hACE2 through the administration of an adeno-associated virus vector or recombinant Adenovirus [2,[15][16][17][18][19][20][21][22]. While in the current study we chose low dose administration of virus to focus on immune responses future studies with higher doses of virus, similar to those published in other mouse models [2,[15][16][17][18][19][20][21][22] can be administered to determine the utility of this model for SARS-CoV-2 pathogenesis.…”
Section: Viral Replicationmentioning
confidence: 99%
See 2 more Smart Citations
“…While these studies suggest that the hACE2 mRNA transfection into the Ifnar1 -/mice did not increase the susceptibility of the Ifnar1 -/mice to SARS-CoV-2 it is possible that the dose and route of infection as well as the harvest time points we chose for these studies were not optimal for detection of infectious virus. Previous studies have shown that administration of higher doses of virus by the intranasal route did lead to the detection of virus in mice which had been induced to express hACE2 through the administration of an adeno-associated virus vector or recombinant Adenovirus [2,[15][16][17][18][19][20][21][22]. While in the current study we chose low dose administration of virus to focus on immune responses future studies with higher doses of virus, similar to those published in other mouse models [2,[15][16][17][18][19][20][21][22] can be administered to determine the utility of this model for SARS-CoV-2 pathogenesis.…”
Section: Viral Replicationmentioning
confidence: 99%
“…As was shown for SARS-CoV [13], specific interactions between the spike glycoprotein, specifically the receptor binding motif of SARS-CoV-2 and hACE2, likely explain why SARS-CoV-2 infection of wild type mice does not occur [8]. Therefore, to establish a susceptible mouse model to study pathogenesis and immune responses to SARS-CoV-2, we must either alter the SARS-CoV-2 virus to recognize the mACE2 [14] or express the hACE2 in mice [2,[15][16][17][18][19][20][21]. Various strategies have been employed by multiple groups to facilitate the expression of hACE2 in mice, from CRISPR/Cas9 mediated hACE2 transgenics [2,15,[18][19][20][21], to adenovirus [16] or adeno associated virus (AAV) expressing hACE2 [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 K18 hACE2 transgenic mice [B6.Cg-Tg(K18-ACE2)2Prlmn/J] are susceptible to SARS-CoV-1 infection 11 and recent reports suggest that K18 hACE2 transgenic mice can also be infected with SARS-CoV-2. 12,13 hACE2 expression in K18 hACE2 transgenic mice is driven by the human cytokeratin 18 (K18) promoter. 11 Importantly, hACE2 expression in K18 hACE2 transgenic mice is observed in airway epithelial cells where SARS-CoV-1 and SARS-CoV-2 infections are typically initiated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research indicates that hACE2-expressing mice are useful for studies related to SARS-CoV-2 pathogenesis and COVID-19. [12][13][14][15][16] A validated rodent model of SARS-CoV-2 infection could help to accelerate testing of vaccines (prophylactic) and antivirals (therapeutic) for the prevention and treatment, respectively, of SARS-CoV-2 infection and associated severe COVID-19 disease. Compared to large animals, a murine model would have desirable features of tractability, ease of use and availability, be cost efficient and permit mechanistic studies to identify attributes of severe COVID-19 outcomes in some but not all people who are infected.…”
Section: Introductionmentioning
confidence: 99%